2005
DOI: 10.1111/j.1365-2958.2005.04728.x
|View full text |Cite
|
Sign up to set email alerts
|

Large increases in attractant concentration disrupt the polar localization of bacterial chemoreceptors

Abstract: SummaryIn bacterial chemotaxis, the chemoreceptors [methylaccepting chemotaxis proteins (MCPs)] transduce chemotactic signals through the two-component histidine kinase CheA. At low but not high attractant concentrations, chemotactic signals must be amplified. The MCPs are organized into a polar lattice, and this organization has been proposed to be critical for signal amplification. Although evidence in support of this model has emerged, an understanding of how signals are amplified and modulated is lacking. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
54
1

Year Published

2008
2008
2013
2013

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 49 publications
(64 citation statements)
references
References 82 publications
(148 reference statements)
9
54
1
Order By: Relevance
“…It has been reported that Escherichia coli exhibits metabolism-dependent chemotaxis towards glycerol [26]. Rhodobacter sphaeroides shows chemotaxis towards a wide range of amino acids, organic acids, and sugars [27]. Metabolism-dependent chemotaxis is similar to other bacterial behavioral responses collectively known as energy taxis, defined as a behavioral response to stimuli affecting cellular energy levels [28].…”
Section: Resultsmentioning
confidence: 99%
“…It has been reported that Escherichia coli exhibits metabolism-dependent chemotaxis towards glycerol [26]. Rhodobacter sphaeroides shows chemotaxis towards a wide range of amino acids, organic acids, and sugars [27]. Metabolism-dependent chemotaxis is similar to other bacterial behavioral responses collectively known as energy taxis, defined as a behavioral response to stimuli affecting cellular energy levels [28].…”
Section: Resultsmentioning
confidence: 99%
“…Specifically, the diffuse staining previously observed is likely due to the formation of lateral clusters. As a consequence, we were able to extend and refine the observations concerning McpB localization made by Lamanna et al (12).…”
Section: Attractant Binding Reduces the Number Of Polar Receptor Clusmentioning
confidence: 86%
“…Our approach was similar to the one employed by Lamanna et al (12), although we refined their analysis to take into account recent observations in E. coli regarding the positioning of the receptor clusters. Although the majority of receptors are localized at the poles in E. coli, many are also found in distinct clusters laterally along the length of the cell (7-9, 37, 39 -41).…”
Section: Attractant Binding Reduces the Number Of Polar Receptor Clusmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the interpretation of these results is far from simple, they do seem congruent with a previous study in which cells were exposed to high concentrations of attractant. Once again, the chemotaxis receptors were dispersed (17).…”
mentioning
confidence: 99%